Revisiting Ibn Khaldun's Arabic Language Education Theory: A Pedagogical Framework for Contemporary Learning - Pradi Khusufi Syamsu; Muhamad Towil Akhirudin (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Contemporary Arabic language education faces a serious pedagogical crisis: the dominance of grammatical rote learning, the absence of immersive language environments, and the failure to integrate socio-cultural dimensions into curricula. Despite numerous studies on Ibn Khaldun's thought, no research has constructed a unified, operational pedagogical framework from his work. This study aims to construct a comprehensive pedagogical framework from Ibn Khaldun's Arabic language education theory in Al-Muqaddimah and elaborate its relevance for contemporary Arabic language learning. Employing a qualitative approach with a systematic literature review (SLR) design and thematic-comparative content analysis, this study examines the primary source Al-Muqaddimah alongside 76 secondary sources in Indonesian and English, collected via Google Scholar, SINTA, and Scopus. Source triangulation ensures data trustworthiness. The study identifies six pedagogical pillars in Ibn Khaldun: malakah (linguistic habitus), tadarruj (gradual staging), tikrār (structured repetition), munāẓarah (scholarly dialogue), riḥlah (authentic experience), and asabiyyah (socio-cultural ecology). These pillars correspond profoundly to Vygotsky's scaffolding, spaced repetition, CLT, Kolb's experiential learning, and Wenger's community of practice — establishing Ibn Khaldun as a pedagogical pioneer six centuries ahead of these theories. This study contributes an operational six-pillar pedagogical framework and identifies asabiyyah as a critically neglected pedagogical variable, with implications for Arabic language curriculum reform and the design of digital learning platforms.